The Significance Of The Polymorphic Marker Aluins / Dell> D Of The Ace Gene In The Development Of Diabetic Nephropathy - Jabbarov О.О; Sapayeva Z.A (Zien Journals, 2022)
This article presents the results of a study of 129 patients with type 2 diabetes and 110 healthy people to determine whether the polymorphic markers AluIns / Dell> D of the ACE gene are associated with the development of diabetic nephropathy (DN). Patients in the main group: 65 patients with a disease duration of up to 10 years, without diabetic nephropathy (33 patients) and with diabetic nephropathy (32 patients), 64 patients with diabetes lasting more than 10-20 years, with no diabetic nephropathy (31 patients ) and diabetic nephropathy (33 patients). Genotyping was carried out using the polymerase chain reaction method. The study showed that the association of the D allele and the heterozygous I/D genotype of the ACE gene play a role in the development of diabetic nephropathy in patients with type 2 diabetes mellitus in the studied Uzbek nation.
Keywords: diabetic nephropath; diabetes mellitus; gene; polymorphism